(untitled) (Journal of Engineering, 2021)
Asphalt Hot Mix (HMA) is mainly applied in highway construction in Iraq because of its economic advantage and easy maintenance. Various factors impact the performance of HMA in the field. It is one of the significant impacts on aggregate gradation. The Universal Specification for Roads and Bridges in Iraq (SCRB) limits the different types of asphalt layers and allows for designed tolerance aggregate gradation. It is quite hard for contractors in the present asphalt industries to achieve the required job mix because of sieves’ control problems. This study focuses on the effects on the required specification performance of aggregate deviations by using original and modified asphalt binder with AC(40-50) and 4% SBS, respectively. A mid gradation of the base asphalt mixture was selected as a reference mix, and more than 24 deviated mixtures were then prepared. Typical Marshall routine studies on prepared compounds were performed to assess the properties of the mixture. Bailey’s theory (CA, Fac ratios) was also employed for understanding the impact of these deviations on the arrangement of particles and blending performance. Results show that the mixture performance is not affected greatly by minor aggregate deviations. However, a significant deviation in coarse aggregates leads to a decrease in Marshall properties. Results showed that a good tool for understanding mixing performance is the Bailey performance assessment method. This paper aims to study the effects of using 4% Styrene Butadiene Styrene (SBS) and eliminating the effect of aggregate gradation deviations on the mixture performance.